Representative democracy - its meaning and basic principles: Array - Haxhiu, Sadik; Alidemaj, Avni (Acta Universitatis Danubius. Juridica, 2021)
The notion of representative democracy and its decomposition is quite difficult and very complex. It has an ancient genesis of its appearance and development which dates back to Hellenic civilization, while its evolution results after the overthrow of the absolutist power of monarchies and the beginning of the election of the first representative bodies by the people's vote. At this time, the division of state power into three levels is unfolded as: the representative-legislative power, led by the representatives elected by the people; executive power, led by the monarch and government and judicial power, led by the courts. The separation of powers system has paved the way for its development and consolidation which is realized through its theological principles: Equality of all citizens before the law; The legitimacy of state power; Realization of popular sovereignty; Participation in public life; Majority rule and minority rights; Protection and respect for human rights; Political pluralism; Free and fair elections; Separation and restriction of power. This paper discusses the contemporary challenges of the manifestation of representative democracy using intertwined scientific methods such as: analytical, comparative, historical and qualitative method.